Cover crop influence on pore size distribution and biopore dynamics: Enumerating root and soil faunal effects - Lucas, Maik; Nguyen, Linh T. T.; Guber, Andrey; Kravchenko, Alexandra N. (Frontiers in Plant Science, 2022)
Pore structure is a key determinant of soil functioning, and both root growth and activity of soil fauna are modified by and interact with pore structure in multiple ways. Cover cropping is a rapidly growing popular strategy for improving agricultural sustainability, including improvements in pore structure. However, since cover crop species encompass a variety of contrasting root architectures, they can have disparate effects on formation of soil pores and their characteristics, thus on the pore structure formation. Moreover, utilization of the existing pore systems and its modification by new root growth, in conjunction with soil fauna activity, can also vary by cover crop species, affecting the dynamics of bio-pores (creation and demolition). The objectives of this study were (i) to quantify the influence of 5 cover crop species on formation and size-distribution of soil macropores (>36 µm Ø); (ii) to explore the changes in the originally developed pore architecture after an additional season of cover crop growth; and (iii) to assess the relative contributions of plant roots and soil fauna to fate and modifications of bio-pores. Intact soil cores were taken from 5 - 10 cm depth after one season of cover crop growth, followed by X-ray computed micro-tomography (CT) characterization, and then the cores were reburied for a second root growing period of cover crops to explore subsequent changes in pore characteristics with the second CT scanning. Our data suggest that interactions of soil fauna and roots with pore structure changed over time. While in the first season large biopores were created at the expense of small pores, in the second year these biopores were reused or destroyed by the creation of new ones through earthworm activities and large root growth. In addition, the creation of large biopores (>0.5 mm) increased total macroporosity. During the second root growing period, these large sized macropores, however, are reduced in size again through the action of soil fauna smaller than earthworms, suggesting a highly dynamic equilibrium. Different effects of cover crops on pore structure mainly arise from their differences in root volume, mean diameter as well as their reuse of existing macropores.